Investing in traditional medicine: leveraging evidence and innovative research to strengthen the fight against malaria in Nigeria - Francisca Ogochukwu Onukansi; Collins Chibueze Anokwuru; Stanley Chinedu Eneh; Goodness Ogeyi Odey; Dough Owojoku Onah; Taiwo Sokunbi; David Chinaecherem Innocent; Ugonma Winnie Dozie; Prince Christian Umoke; Temitope Olumuyiwa Ojo; Cosmas Nnadozie Ezejindu (Malaria Journal)
Abstract Traditional medicine (TM) has been a cornerstone of healthcare across various cultures, especially in Africa, where it has played an integral role in the management of diseases such as malaria. Despite the popularity and historical significance of TM, scientific validation remains a key challenge, hindering its widespread acceptance in modern healthcare systems. This study explores the potential of traditional African medicine, particularly in the context of Nigeria, as a vital resource in the fight against malaria. Drawing on the success of plants like Artemisia annua in the development of modern anti-malarial drugs, the research emphasizes the need for comprehensive investment in TM research. With Nigeria facing the highest malaria burden globally, the research advocates for increased funding, scientific investigations into the efficacy of traditional remedies, and enhanced regulation of herbal medicine. The paper also highlights the growing trust and reliance on herbal remedies in rural areas of Nigeria and the importance of ensuring their safety through pharmacological testing. This study examines these issues through an analysis of existing literature, historical applications, and documented successes of herbal treatments. By integrating traditional medicine into national health systems, Nigeria could unlock new strategies for combating malaria and other infectious diseases, advancing toward sustainable health outcomes.